Internalization of Environmental Values, Local Wisdom, and Sustainable Development Goals (SDGs) Issues - Giyono; Suyitno (The Indonesian Institute of Science and Technology Research, 2024)
This study aims to explain the importance of internalizing environmental values based on local wisdom in supporting the achievement of the Sustainable Development Goals (SDGs). These values not only encourage environmental awareness, but also play a role in creating a balance between economic, social, and environmental aspects of sustainable development. The approach used in this study is descriptive qualitative, combining the author's opinions and experiences and supported by relevant secondary sources, such as literature and previous research. The results of the study indicate that local wisdom, through traditional practices such as community-based forest management and organic farming, supports ecosystem preservation and community empowerment in sustainable decision-making. Internalizing environmental values helps communities become more aware of the impact of human activities on the environment and more active in mitigating climate change and conserving natural resources. Based on these findings, it is recommended that environmental education and development policies better integrate local wisdom, to create more inclusive and sustainable development. This is important to ensure that the achievement of the SDGs does not only focus on economic growth but also ecosystem sustainability and social welfare.